Fulvifomes parviungulatus (Hymenochaetales, Basidiomycota), a new species from China based on morphological and molecular evidence - Ji, Xiao-Hong; He, Gang; Sun, Qi-Biao; Chen, Ye (Phytotaxa, 2024)
Fulvifomes parviungulatus sp. nov. is described and illustrated from China based on morphological characters and phylogenetic analyses. The sequences of the internal transcribed spacer (ITS) region and nuclear-encoded large subunit rRNA gene (28S) were employed. Fulvifomes parviungulatus is characterized by the perennial, small and ungulate basidiocarps, crusted, smooth pileal surface, 4–5 pores per mm with thick dissepiments, a dimitic hyphal system with interwoven skeletal hyphae, absence of ventricose cystidioles, collapsed hymenium in the studied material and ellipsoid, yellowish brown, thick-walled, smooth basidiospores measuring 4.2–4.7 × 3.5–4 μm. The new species was compared with its related taxa and a molecular study supports it with in the genus of Fulvifomes.